Environment, Population, and Economy on CO2 Emission in Indonesia - Cahyo, Heru; Purnomo, Sodik Dwi; Octisari, Sully Kemala; Surveyandini, Mayla; Sundari, Sri; Purwendah, Elly Kristiani (International Journal of Energy Economics and Policy, 2023)
Recent years have seen a significant escalation in the environmental issue of climate change brought on by rising CO2 emission levels. Global warming and rising temperatures have the potential to cause ecological harm. The rising greenhouse gas (GHG) emissions on Earth can contribute to global warming. One of the most significant factors in CO2 output is the likelihood of disasters, which is increased by rising temperatures. The purpose of this study is to ascertain the impact of the environment (forest area), population (urbanization & motorized vehicle usage), and economy (industrialization & exports) on CO2 emission in Indonesia from 1990 to 2021. The data was gathered from the Central Bureau of Statistics, International Energy Agency, and World Bank and is secondary data in the form of time series data. Multiple linear regression is the study methodology. The findings demonstrated that the amount of forest area, urbanization, and industrialization are negative and significant on Indonesia’s CO2 emissions. Meanwhile, Indonesia’s CO2 emissions are positively and significantly affected by the number of motorized vehicles and exports. Green and renewable energy must be used in various industries to execute policies that reduce CO2 emissions.